Pareceristas deste volume - tempos, outros (Outros Tempos: Pesquisa em Foco - História, 2009)
André Nunes de Azevedo (UERJ); Elizabeth Sousa Abrantes (UEMA); Helidacy Maria Muniz Corrêa (UEMA); Júlia Constança Pereira Camêlo (UEMA); Lucilene Reginaldo (UEFS); Mairton Celestino (UFPI); Marcelo Cheche Galves (UEMA); Marcelo de Souza Magalhães (UERJ); Martha Abreu (UFF); Maria Mirtes dos Santos Barros (UFMA); Paulo Roberto Rios Ribeiro (Fac.São Luís-MA); Rafael Ivan Chambouleyron (UFPA); Régia Agostinho da Silva(UFMA); Regina Helena Martins de Faria (UFMA); Reinaldo dos Santos Barroso Junior (UEMA); Sandra Regina Rodrigues dos Santos (UEMA); Théo Lobarinhas Piñeiro (UFF); Yuri Costa (UEMA).